Training Need Analyses of Educators and Education Personnel Based on Educational Report Card at SMK N 1 Nanggulan, Kulon Progo Regency - Iin Widiyastuti (PT. Anagata Sembagi Education, 2024)
The demands of technological development are also felt by in the world of education. The Education Report Card is the result of scores from the performance of the Education unit. From these results, an evaluation is carried out on which indicators have insufficient value and need improvement. There is a red value on the quality indicator of human resource management at SMKN 1 Nanggulan so further analysis is required in order to explore the training needs that must be implemented. Research Method was carried out by interviews with key informants. The research was carried out at SMKN 1 Nanggulan in Kulon Progo district. The purpose of writing this article is to determine the